Ta'ṡīr Istikhdām Wasīlati al Kitābi al Kabīri (Big Book) fi Taḥsīni Mahārati al Qirā’ati lada al Ṭullābi Faṣli al Ṡani bi al Madrasati al Ibtidā’iyyati al Islāmiyyati al Ḥukūmiyyati 5 Agam - Elvi Sonya, Elvi; Nurhasnah, Nurhasnah; Refdianti, Afrina (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2023)
This aeticle discusses the effect of big book media in improving the reading skills of class 2 students at Islamic elementary school 5 Agam. In this research , the writer discusses Arabic. The problems encountered are that students are hesitant to pronounce hijaiyyah letters so they don’t like to read, the text and images in student bool are less attractive because of their small size. This study aims to enable students to pronounce hijaiyyah letters and students can read texts correctly. This study used the Pre Experimental method (One Group Pretesr- Posttest Design). The sampling techniquw is Nonprobability Sampling. The population in this study were all class 2 students at Islamic elementary school 5 Agam total sample of 14 students. The sampling technique is Nonprobability Sampling namely (sampling jenuh) because there are less than thirty students. Data collection tools used are tests, observations and interviews. Perform data analysis using Paires Sample Test with the help of IBM SPSS Statistics V.20 for windows. The results showed that the average pre- test was 69, after using the big book media, the average post-test score was 78.5714. The results of data analysis showed that the t count was 9.862 and the t table was 2,160. This means that T count is greater than t table. Thus H0 is rejected while Ha is accepted. So it can be concluded that the big book media has an effect on improving students reading skills.